2022
DOI: 10.1093/hmg/ddac124
|View full text |Cite
|
Sign up to set email alerts
|

Identifying candidate genes and drug targets for Alzheimer’s disease by an integrative network approach using genetic and brain region-specific proteomic data

Abstract: Genome-wide association studies (GWAS) have identified more than 75 genetic variants associated with Alzheimer’s disease (ad). However, how these variants function and impact protein expression in brain regions remains elusive. Large-scale proteomic datasets of ad postmortem brain tissues have become available recently. In this study, we used these datasets to investigate brain region-specific molecular pathways underlying ad pathogenesis and explore their potential drug targets. We applied our new network-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…EW_dmGWAS is an advanced iteration of the dmGWAS tool, which can integrate gene expression data by applying weighted edges of differential gene co-expression, offering a refined exploration of disease-related genetic and epigenetic interplays. Liu et al conducted an integrative proteomics and GWAS study to investigate the molecular pathways in brain-specific regions to recognize causal genes in AD pathogenies [ 71 ]. While the current study focused on the epigenetic mechanisms occurring in AD, succeeding studies integrating genetic, proteomic, and epigenomic data may provide a more holistic view of AD’s molecular landscape.…”
Section: Discussionmentioning
confidence: 99%
“…EW_dmGWAS is an advanced iteration of the dmGWAS tool, which can integrate gene expression data by applying weighted edges of differential gene co-expression, offering a refined exploration of disease-related genetic and epigenetic interplays. Liu et al conducted an integrative proteomics and GWAS study to investigate the molecular pathways in brain-specific regions to recognize causal genes in AD pathogenies [ 71 ]. While the current study focused on the epigenetic mechanisms occurring in AD, succeeding studies integrating genetic, proteomic, and epigenomic data may provide a more holistic view of AD’s molecular landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Among the common variants, the APOE4 allele is the strongest risk factor, with individuals with this variant showing higher odds for AD with one APOE4 allele (odds ratio [OR] 4.6 [95% confidence interval (CI) 4.1-5.2]) or two APOE4 alleles (OR ) compared with those without the APOE4 allele [17]. However, APOE alone does not fully explain the development of LOAD; as a result, ongoing research has been carried out to investigate additional genetic factors and pathways that play a role in both the development and resilience of AD [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, individuals with high education attainment had a lower risk of AD and lower cognitive decline, even if they have a high PRS for AD [21]. Several theories [19,21] have been proposed to explain a few resilience metrics that were genetically correlated with these counterfactors and mitigate the effect of genetic risk on AD development. For example, Dumitrescu et al [19] conducted GWAS for validated metrics of cognitive resilience and identified a genome-wide significant locus near ATP8B1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reasons for this difficulty are the selection of low-accuracy target genes based mainly on animal studies and the start of the drug discovery process with insufficient stratification of patients to be treated. Therefore, efforts are being made in target gene searches to promote new drug discovery targets based on human or other data [14][15][16]. It is expected that the use of human data such, as omics data and clinical information, can reduce failures due to reliance on animal testing [17,18].…”
Section: Introductionmentioning
confidence: 99%